Cultural Transformation and Values of the Puputan Bayi Tradition in Medan: An Anthropological Approach - Manik, Yesy Novirnati; Safriza, Nazua; Pajila, Najwa; Malau, Rico; Tambunan, Bony Charlos; Septriani, Septriani (Yayasan Tri Edukasi Ilmiah, 2024)
This study aims to analyze the cultural transformation and values in the puputan bayi tradition in Medan using an anthropological approach. Applying Giddens’ (2013) theory of social change, the research focuses on how this tradition adapts and evolves alongside social and cultural developments influenced by modernity and globalization. This study employs a qualitative method with data collection techniques including in-depth interviews, participant observation, and document analysis. The informants consist of traditional leaders, families who practice the tradition, and local community members directly involved in the puputan bayi ceremony. The findings reveal that while traditional values are preserved, adjustments in the practice of the puputan bayi tradition reflect the influence of social changes, including aspects of gender roles, family participation, and the understanding of ritual meanings. The study also reveals that the people of Medan, particularly those of Javanese and Batak ethnicity, demonstrate openness to integrating modern values into their traditional practices. This cultural transformation reflects a process of acculturation and integration between local and global values, shaping a new social identity within urban communities.